Perbandingan nilai rasio neutrofil-limfosit dan kadar c-reactive protein dengan kultur darah positif dan kultur darah negatif pada penderita systemic inflammatory response syndrome - Hilda Sungkar; Muzahar dr; Ricke Loesnihari (Fakultas Kedokteran USU, 2017)
Introduction : Systemic Inflammatory Response Syndrome (SIRS) is a non specificreaction that could be caused by infection, inflammation, or acombination of both factors.Bacteremia detectionin SIRS patientsis a challenge forclinicians. Neutrophil-lymphocyte count ratio (NLCR) and C-reactive protein (CRP) could rapidly predict bacteremia.Method : Thiscross sectional study was conducted in Emergency Unit RSUPH.Adam Malik Medan from January to March 2016. Patients that met SIRS criteria had their NLCR, CRPand blood culture tested.Result : Of 48 samples, 21 (43.75%) were male and 27 (56.25%) were female.In this study, there was significant difference of NLCR from both groups, where NLCR in SIRS with positive blood culture was higher that SIRS with negative blood culture(38.16 ± 34.97vs9.68 ± 5.26, P=0.001). There wasa significant difference between CRP in both groups. CRP in SIRS with positive blood culture was higher than SIRS with negative blood culture. (5.89 ± 3.09vs 3.15 ± 1.89, p = 0.001).Conclusions : There is significant difference of NLCR and CRP in SIRS patients with positive and negative blood culture. RNL and CRP could be used as a marker for detecting bacteremia in SIRS patients.Keywords : Neutrophil to Lymphocyte Count Ratio, C-Reactive Protein, Systemic Inflammatory Response Syndrome